Pifithrin-μ sensitizes mTOR-activated liver cancer to sorafenib treatment - Jiarui Lv; Yanan Wang; Jiacheng Lv; Cuiting Zheng; Xinyu Zhang; Linyan Wan; Jiayang Zhang; Fangming Liu; Hongbing Zhang (Cell Death and Disease)
Abstract TSC2, a suppressor of mTOR, is inactivated in up to 20% of HBV-associated liver cancer. This subtype of liver cancer is associated with aggressive behavior and early recurrence after hepatectomy. Being the first targeted regimen for advanced liver cancer, sorafenib has limited efficacy in HBV-positive patients. In this study, we observed that mTOR-activated cells, due to the loss of either TSC2 or PTEN, were insensitive to the treatment of sorafenib. Mechanistically, HSP70 enhanced the interaction between active mTOR-potentiated CREB1 and CREBBP to boost the transcription of the antioxidant response regulator SESN3. In return, elevated SESN3 enhanced cellular antioxidant capacity and rendered cells resistant to sorafenib. Pifithrin-μ, an HSP70 inhibitor, synergized with sorafenib in the induction of ferroptosis in mTOR-activated liver cancer cells and suppression of TSC2-deficient hepatocarcinogenesis. Our findings highlight the pivotal role of the mTOR-CREB1-SESN3 axis in sorafenib resistance of liver cancer and pave the way for combining pifithrin-μ and sorafenib for the treatment of mTOR-activated liver cancer.